ANALISIS NILAI MORAL DALAM CERITA PENDEK TOA KARYA HERUMAWAN P.A. : KAJIAN SEMIOTIK SASTRA - Rika Eliyana; R Ika Mustika; Diena San Fauziya (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is the result of a descriptive study that examines a short story entitled "Toa" by Herumawan P.A through Pierce's semitoic approach. In general, this study aims to determine the system of signs and implicit meanings that represent the correlation of meaning and moral life in the short story. The type of research used is descriptive qualitative using Pierce's semiotic theory which refers to icons, indexes, and symbols. The data source in this research is the short story text Toa by Putu Herumawan P.A. The data accumulation system used is a literature studyÂ  with analysys content, that is, to directly make an analysis. The data analysis system using analyzing system, the consists of three series of activity that occur continuously from data reduction and core conclusions.